Wymagania i zasoby w pracy nauczycielek i nauczycieli w czasie pandemii COVID-19. Implikacje dla aktualnych wyzwań zawodu nauczyciela - Jaskulska, Sylwia (Studia Edukacyjne, 2025)
The aim of the article is to explore how the relationship between job demands and resources shaped teachers’ professional experiences during the COVID-19 pandemic, as well as to identify what conclusions from that period may be useful in the context of contemporary and future challenges related to the teaching profession. The article based on the review of scientific research employing the Job Demands–Resources (JD-R) model to analyze teachers’ professional work during the COVID-19 pandemic. Evidence suggests that the pandemic significantly altered the working conditions of teachers, increasing both the number and intensity of didactic and emotional demands. Resources like social support, a sense of control, digital competencies, and personal traits like resilience and optimism played a crucial role. The Job Demands Resources model provides a framework for understanding the relationship between these resources and the heightened demands of the pandemic period. The article emphasizes the importance of pandemic-era research in understanding the contemporary challenges of the teaching profession. The author argues that pandemic experiences offer valuable insights into the relationship between job demands and resources and underscores the need to continue efforts to strengthen resources amid growing teachers’ work demands.